Stomatal uptake and stomatal deposition of ozone in isoprene and monoterpene emitting plants - Fares, S.; Loreto, F.; Kleist, E.; Wildt, J. (Plant Biology, 2008)
Volatile isoprenoids were reported to protect plants against ozone. To understand whether this could be the result of a direct scavenging of ozone by these molecules, the stomatal and non-stomatal uptake of ozone was estimated in plants emitting isoprene or monoterpenes. Ozone uptake by holm oak (Quercus ilex, a monoterpene emitter) and black poplar (Populus nigra, an isoprene emitter) was studied in whole plant enclosures (continuously stirred tank reactors, CSTR). The ozone uptake by plants was estimated measuring ozone concentration at the inlet and outlet of the reactors, after correcting for the uptake of the enclosure materials. Destruction of ozone at the cuticle or at the plant stems was found to be negligible compared to the ozone uptake through the stomata. For both plant species, a relationship between stomatal conductance and ozone uptake was found. For the poplar, the measured ozone losses were explained by the uptake of ozone through the stomata only, and ozone destruction by gas phase reactions with isoprene was negligible. For the oak, gas phase reactions of ozone with the monoterpenes emitted by the plants contributed significantly to ozone destruction. This was confirmed by two different experiments showing a) that in cases of high stomatal conductance but under low CO2 concentration, a reduction of monoterpene emission was still associated with reduced O3 uptake; and b) that ozone losses due to the gas phase reactions only can be measured when using the exhaust from a plant chamber to determine the gas phase reactivity in an empty reaction chamber. Monoterpenes can therefore relevantly scavenge ozone at leaf level contributing to protection against ozone.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: isoprene; Monoterpenes; Ozone uptake; photosynthesis; reaction chambers; Stomatal conductance